Assessment of the pH of water and sediments at Ramsar Sites in Gabes city, Tunisia - Slaheddine Bessadok, Abdelhak Rhouma, Naoufel Hamouda (Journal of Ecobiotechnology, 2017)
Very few studies of the potential of Hydrogen (pH) of water and sediment wetland at Ramsar site 2076/2012 have been reported in the literature. In this context, a sampling was collected from five sites of Oued El Malah and Tarf El Maa (north of Gabes: south-east of Tunisia). The results showed that the pH complies with national and international regulations (6.5 ?pH ? 8.5). Indeed, the hydrogen potential of water was varied between 7.88 (S2) and 8.24 (S1). It is ranged from 7.76 (S1 and S2) to 8.05 (S4) for sediments. Positive correlation (r = 0.985) and highly significant difference (P <0.01) were recorded for water and sediment pH. To confirm or refute this hypothesis, additional studies (physicochemical, biochemical and bacteriological analysis) are needed to assess the quality of these areas.